2008
DOI: 10.1094/mpmi-21-4-0411
|View full text |Cite
|
Sign up to set email alerts
|

The rsmA-like Gene rsmAXcc of Xanthomonas campestris pv. campestris Is Involved in the Control of Various Cellular Processes, Including Pathogenesis

Abstract: RsmA is an RNA-binding protein functioning as a global post-transcriptional regulator of various cellular processes in bacteria and has been demonstrated to be an important virulence regulator in many animal bacterial pathogens. However, its function in other phytopathogenic bacteria is unclear, except for the Erwinia carotovora RsmA, which acts as a negative virulence regulator. In this work, we investigated the function of the rsmA-like gene, named rsmA(Xcc), of the phytopathogen Xanthomonas campestris pv. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 74 publications
2
60
0
9
Order By: Relevance
“…Recently, we have demonstrated that RsmA and DsbB of X. campestris pv. campestris, which are required for full virulence, are involved in various cellular processes, including cell motility (10,30). More recently, it has been shown that the virulence-deficient mutants derived from a mutation in the genes XC_2249 and XC_3221 of the X. campestris pv.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have demonstrated that RsmA and DsbB of X. campestris pv. campestris, which are required for full virulence, are involved in various cellular processes, including cell motility (10,30). More recently, it has been shown that the virulence-deficient mutants derived from a mutation in the genes XC_2249 and XC_3221 of the X. campestris pv.…”
Section: Discussionmentioning
confidence: 99%
“…campestris and X. axonopodis pv. citri pathovars (100,358). In both cases, RsmA promoted virulence through the activation of genes associated with a T3SS.…”
Section: Plant Pathogensmentioning
confidence: 99%
“…campestris and significantly reduces the hypersensitive response in nonsusceptible hosts (358). Deletion of rsmA significantly reduced motility and the extracellular levels of virulence factors, including endoglucanase, amylase, and extracellular polysaccharide (EPS) (also called "xanthan gum").…”
Section: Plant Pathogensmentioning
confidence: 99%
“…In both strains, deletion of rsmA led to a loss of pathogenicity, which was associated with an altered expression of hrp-and rpf-genes. [51][52][53] These mutants also showed pleiotropic phenotypes, e.g., higher levels of intracellular glycogen, increased bacterial adhesion and aggregation, and reduced production of extracellular enzymes. [51][52][53] RsmA in Xanthomonas spp.…”
Section: 38mentioning
confidence: 99%